Pemanfaatan Karbon Aktif Daun Serai (Cymbopogon citratus) dan Bleaching Earth dalam Penjernihan Minyak Jelantah - Yanti, Fetria Rahayu Wendi; Nizar, Umar Kalmar (MASALIQ, 2025)
Used cooking oil is a household waste with the potential to pollute the environment and pose health risks if discarded improperly or reused without adequate treatment. This study aims to purify used cooking oil through a two-stage adsorption method using activated carbon derived from lemongrass leaves and Bleaching Earth. In the first stage, activated carbon was synthesized from lemongrass leaves calcined for 60 minutes and activated with 2N NaOH solution, followed by the addition of Bleaching Earth in the second stage. The quality of the oil before and after purification was assessed through analyses of density, acid number, saponification value, moisture content, and infrared spectrum (FTIR). The results indicate that activated carbon calcined for 60 minutes (MJ-C60) yielded the best outcome, reducing density to 0.9414 g/mL, lowering moisture content from 0.34% to 0.16%, and increasing the saponification value from 41.5650 to 63.7075 mg KOH/g. The acid number also decreased from 13.2302 to 8.3288 mg KOH/g. FTIR analysis revealed the presence of ester C=O groups around 1743 cm⁻¹ and aliphatic C–H absorption bands at 2850–2950 cm⁻¹, indicating that the triglyceride structure remained intact. These findings demonstrate that the combination of activated carbon from lemongrass leaves and Bleaching Earth is effective in improving the clarity and physicochemical quality of used cooking oil, while offering an environmentally friendly solution based on organic waste utilization.